Problem Solving Skills among Adolescents in Surat City: A Reality Check - Mohua Moitra; Rutu Buch; Rahul Damor (Medsci Publications, 2019)
Introduction: Adolescents pass through physical, mental and social development. Problem solving skill is necessary to address the problems in daily life. The present study was conducted to estimate the 'problem solving' skills among adolescents and the factors affecting it. Methods: A cross sectional study using purposive sampling was carried out involving 1177 college going students aged between 17 and 19 years. General Self Efficacy (GSE) Scale and semi-structured questionnaire was used to collect data. Statistical analysis was conducted with the help of SPSS. Results: Problem solving skill was good (score>31) among 58.4% and fair (score<30) among 41.6% of participants. Mean (SD) and median score was 31.2 (SD-4.1) and 31.5 (Range between 17 and 40). Cronbach's alpha was 0.7. Problem solving skills were affected by sex, score on fantasy scale, levels of empathic concern, perspective taking, levels of personal distress, decision making process, skill for coping with stress and creative thinking Conclusion: Life skill based education contributes in the emotional and behavioural development of adolescents leading to better problem solving skills. Thus life skill education/training is the need of the hour to empower this vulnerable group to deal with the various challenges faced by them.